ИЗУЧЕНИЕ В КАРАКАЛПАКСКОЙ ФОЛЬКЛОРИСТИКЕ ИСТОРИЧЕСКИХ ПЕСЕН КАРАКАЛПАКСКОГО НАРОДА - Турдыев, Б. (SCIENCE and SOCIETY, 2022)
The article is devoted to the study of historical songs of Karakalpak folklore. The ancient and rich history are briefly described of the Karakalpak people, national culture, unique art, classical literature, spiritual values and traditions.
Keywords: realistic feature; literary analysis; source; cognitive; extraordinary essays; fundamental classification; chronological ethnographer; Golden Horde